Manfaat dan Konsekuensi Aplikasi E-Government Pemerintah Desa di Kecamatan Kemalang Kabupaten Klaten - Jemino, Jemino (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
After the existence of E-Government regulations in Indonesia, the Village Government was bombarded with various applications that the Village had to run. These applications are from the central, provincial and district governments. With these many applications, there have been various responses from village officials as representatives of the village government. Thus two problems arise. What are the applications in the village administration and how are the benefits of the village administration to these applications. The author uses the method of literature, interviews and documentation for data collection. The descriptive method is used in the presentation of research results with a narrative approach. From the discussion it can be concluded that the most felt benefit from all existing applications is the Siskeudes application. The SGDs application is an application that should be useful for the village but in reality the application is not smooth so the results are also not optimal. While other applications are more of an application for supra-village data. The consequences of this application for the village government are in the form of providing internet access, application operators and computers/laptops. The SGDs and eHDW applications have another consequence in the form of a large additional budget, while the IDM application has another consequence in the form of a lot of filling and involving many parties.